Glioblastoma Multiforme in the Posterior Cranial Fossa in a Patient with Neurofibromatosis Type I. (6th December 2009) - Broekman, Marike L. D.; Risselada, Roelof; Engelen-Lee, JooYeon; Spliet, Wim G. M.; Verweij, Bon H.
Abstract : Patients with Neurofibromatosis type 1 (NF1) have an increased risk of developing neoplasms. The most common brain tumors, found in 15%–20% of NF1 patients, are hypothalamic-optic gliomas, followed by brainstem and cerebellar pilocytic astrocytomas. These tumors generally have a benign nature. NF1 patients are predisposed to a 5-fold increased incidence of high-grade astrocytomas, which are usually located in supratentorial regions of the brain. We present an NF1 patient who developed a high-grade astrocytoma in the posterior fossa and discuss possible pathophysiological mechanisms.